2012
DOI: 10.1104/pp.112.202051
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for the Biosynthesis of the Major Chlorogenic Acids Found in Coffee    

Abstract: (A.A.M.) Chlorogenic acids (CGAs) are a group of phenolic secondary metabolites produced by certain plant species and an important component of coffee (Coffea spp.). The CGAs have been implicated in biotic and abiotic stress responses, while the related shikimate esters are key intermediates for lignin biosynthesis. Here, two hydroxycinnamoyl-coenzyme A shikimate/quinate hydroxycinnamoyl transferases (HCT/HQT) from coffee were biochemically characterized. We show, to our knowledge for the first time, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
135
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 44 publications
12
135
1
3
Order By: Relevance
“…The residue His (H) in the HxxxD motif is important for the enzymatic activity of HCT, and mutation of this amino acid greatly reduces its catalytic activity (Lallemand et al, 2012;Walker et al, 2013). We have shown that mutations at this conserved H residue in HCT1806/4918 did not reduce their ability to suppress Rp1-D21-induced HR (Wang et al, 2015c).…”
Section: Discussionmentioning
confidence: 76%
“…The residue His (H) in the HxxxD motif is important for the enzymatic activity of HCT, and mutation of this amino acid greatly reduces its catalytic activity (Lallemand et al, 2012;Walker et al, 2013). We have shown that mutations at this conserved H residue in HCT1806/4918 did not reduce their ability to suppress Rp1-D21-induced HR (Wang et al, 2015c).…”
Section: Discussionmentioning
confidence: 76%
“…responsible for the biosynthesis and natural variation of benzoylated tryptamine/serotonin. Previous crystal studies have identified several amino acid residues in the N-and C-terminal regions of BAHD acyltransferases important for differential acylacceptor specificity (Ma et al, 2005;Unno et al, 2007;Lallemand et al, 2012;Walker et al, 2013). Here, comparative sequence analysis with in vitro assays using mutant enzymes led to the identification of a RRRR motif that is sufficient to transform agmatine utilization ( Figures 9A and 9B), which is similar to the conserved arginine-rich motifs in RNA binding proteins (Lazinski et al, 1989;Zapp et al, 1991;Yuryev et al, 1996).…”
Section: Discussionmentioning
confidence: 81%
“…The biological significance underpinning the convergent evolution of aryldiamine acyltransferases from both BAHD and GNAT families of proteins, especially within Gramineae, requires further investigation. The 3D structures of some BAHD acyltransferases have been resolved (Ma et al, 2005;Unno et al, 2007;Garvey et al, 2008;Lallemand et al, 2012;Manjasetty et al, 2012;Walker et al, 2013), but no structures are yet available for N-acyltransferases. Elucidation the structure of BAHD N-acyltransferase will greatly facilitate understanding these divergent and convergent evolutionary paths.…”
Section: Discussionmentioning
confidence: 99%
“…BAHD family members share relatively low sequence identity, but nearly all members possess a conserved HxxxD motif (Burhenne et al, 2003). The His in the HxxxD motif is important for the catalytic activity of HCT, and mutation of this residue greatly reduces its activity (Lallemand et al, 2012;Walker et al, 2013). Mutations at this conserved His motif in HCT1806 and HCT4918 did not reduce their ability to inhibit Rp1-D21-induced HR, suggesting that the catalytic activity of HCT1806 and HCT4918 may not be required for their function in regulating Rp1-D21.…”
Section: Discussionmentioning
confidence: 99%
“…4A). The mutation in the His residue of sorghum or coffee (Coffea arabica) HCTs greatly reduced their enzymatic activities (Lallemand et al, 2012;Walker et al, 2013). We thus generated the corresponding mutation in the maize HCT4918: HCT4918(H152A).…”
Section: Not Inhibit Rpm1(d505v)-induced Hr (Supplementalmentioning
confidence: 99%